Does empathy decline in the clinical phase of medical education? A study of students at Leicester medical school - Leila Keshtkar; Andy Ward; Rachel Winter; Char Leung; Jeremy Howick (PEC Innovation)
Objective: To examine whether medical student empathy changes throughout the five years of a UK medical school. Methods: Students completed an online version of the Jefferson Scale of Empathy (JSE-S) during the 2022–2023 academic year. Comparisons of empathy scores were made using analysis of variance (ANOVA), and independent t-tests. Results: Empathy scores varied across different years of medical school (P ≤ 0.001), with a small drop in empathy between the pre-clinical and clinical phases of medical school (Mean difference = 1.82, P = 0.025). Male students scored lower than female students and there was no statistically significant difference between the mean empathy score and speciality interest. Conclusions: Students' empathy appeared declined slightly as they progressed through medical school. As a crucial component of good clinical care, interventions in medical education to enhance empathy should be prioritised. Innovation: This is the first time following the COVID-19 pandemic that medical student empathy was measured across all five years of a medical school. Unlike many previous related studies, we identified the point at which empathy appears to decline, providing guidance for educators who can target empathy enhancing interventions where they are most needed.